(Invited) First-Principles Study on Electron Conduction at 4H-SiC(0001)/SiO2 Interface. (19th August 2016) - Ono, Tomoya; Kirkham, Christopher; Iwase, Shigeru
Abstract : The thermal oxidation process of a hydrogen-terminated 4H-SiC(0001) substrate is examined by performing the first-principles total-energy calculations based on the density functional theory. It is found that the oxidation process of a SiC(0001) substrate is different from that of a Si substrate, which proceeds in a layer-by-layer manner. CO2 molecules are mainly emitted from the SiC surface although CO2 emission becomes less favorable and CO molecules are emitted from the SiC/SiO2 interface. Except for the oxidation energy, the situation is the same with the case of a bare 4H-SiC(0001) surface. We conclude that the effect of the dangling bonds on the surface is marginal and the stress at the interface is responsible for the removal of C during the oxidation.